Prosthetic Joint Infection due to Mycobacterium bovis after Intravesical Instillation of Bacillus Calmette-Guerin (BCG) - Eric Gomez; Tom Chiang; Ted Louie; Madhavi Ponnapalli; Robert Eng; David B. Huang (International Journal of Microbiology)
Intravesical instillation of Bacillus Calmette-Guerin (BCG) is a treatment to prevent recurrence of superficial urothelial bladder carcinoma. Complications after bladder instillation of BCG have been reported including locally invasive and systemic infections due to dissemination of Mycobacterium bovis from the bladder. We present an uncommon case and literature review of prosthetic joint infection due to M. bovis after intravesical BCG treatment of bladder cancer.